1982
DOI: 10.2466/pms.1982.55.3.795
|View full text |Cite
|
Sign up to set email alerts
|

Lucid Dreaming and Alpha Activity: A Preliminary Report

Abstract: 10 good dream recallers spent 2 nights in the sleep lab during which they were awakened 4 times per night from REM sleep, twice during their highest alpha activity in REM, and twice during low REM alpha. 5 were given alpha feedback training prior to sleep onset. Arousals from high alpha REM sleep yielded significantly higher lucidity ratings. Alpha feedback had no effect upon lucidity or REM alpha levels. Similarities between lucid dreams and meditative phenomena are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
1

Year Published

1988
1988
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 7 publications
1
42
1
Order By: Relevance
“…In order to get the best correlates between psychological data (subjects' reports) and physiological data (polysomnography), the data set was split into various 7.5 second epochs. Discriminant function analysis, MANOVA, and ANOVA revealed that the main factor discriminating lucid from non lucid dreams was the beta-1frequency band, which signifi cantly increased during lucid dreaming in the parietal regions of both hemispheres, which is in opposition to the results previously obtained by Ogilvie et al (1978) and Ogilvie et al (1982). The ratio of frontal to parietal beta-1 activity was 1 to 1.16 during non-lucid dreaming and 1 to 1.77 during lucid dreaming.…”
Section: Contemporary Clarifi Cation and Experimentationcontrasting
confidence: 57%
“…In order to get the best correlates between psychological data (subjects' reports) and physiological data (polysomnography), the data set was split into various 7.5 second epochs. Discriminant function analysis, MANOVA, and ANOVA revealed that the main factor discriminating lucid from non lucid dreams was the beta-1frequency band, which signifi cantly increased during lucid dreaming in the parietal regions of both hemispheres, which is in opposition to the results previously obtained by Ogilvie et al (1978) and Ogilvie et al (1982). The ratio of frontal to parietal beta-1 activity was 1 to 1.16 during non-lucid dreaming and 1 to 1.77 during lucid dreaming.…”
Section: Contemporary Clarifi Cation and Experimentationcontrasting
confidence: 57%
“…Other findings, however, suggest that lucidity itself might be associated with high alpha EEG activity (e.g. Ogilvie et al, 1982).…”
Section: Acoustic Stimulationmentioning
confidence: 90%
“…Although it is an interesting idea to associate dream lucidity with alpha activity in the EEG during REM sleep, this causality of this relation seems to be unclear (cf. Ogilvie et al, 1983;Ogilvie et al, 1982) and a possibility of using such biofeedback is a rather complicated method for lucid dream induction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Freud famously said of dreams that they provide privileged access to the workings of the unconscious mind (Freud, 1937) but research on dreaming is fraught with difficulties because [despite the phenomenon of lucid dreaming (Ogilvie et al, 1982)] the dream experience cannot be easily reflected on and reported in real-time, and neither can its onset and offset be easily controlled. Thus, Freud's cherished “royal road” has not proved particularly regal and a more practical alternative is required if key psychoanalytic theories are to be incorporated into the mind sciences.…”
Section: The Research Value Of Psychedelicsmentioning
confidence: 99%